Kolczasty drut śmierci jako strażnik granicy. Nieznany epizod Wielkiej Wojny 1914–1918 na pograniczu holendersko–belgijskim - Żelichowski, Ryszard (Dzieje Najnowsze, 2016)
Abstract: „The Wire of Death as a Border Guard. An Unknown Episode of the Great War 1914–1918 along the Dutch–Belgian Frontier For four long years the First World War changed the relations between the Kingdom of The Netherlands and the Kingdom of Belgium, with the former remaining neutral in the conflict while the latter became a theatre of particularly bloody hostilities. In the province of North Brabant, which was part of the Kingdom of The Netherlands, at a small distance from border with the Kingdom of Belgium there lies a locality bearing the double name of Baarle–Hertog and Baarle–Nassau – a Dutch–Belgian jigsaw composed of 30 enclaves. The German armies decided not to attack the Belgian enclaves since they could not do so without violating the neutrality of the Dutch. In order to prevent the inflow into The Netherlands of volunteers who could come to the aid of the army defending itself in the Yzer river valley, in January 1915 the German troops embarked upon setting up networks of barbed wire along the entire Belgian border (450 kms long) from the Zwin inlet in Knokke to the suburbs of Aix–la–Chapelle. The unique frontier encircling the Belgian enclaves was composed of electric barbed wire known as the „Wire of Death”, which took the lives of numerous victims and was the source of the tragic plight of all thus separated families. The border in question also divided small towns and villages, sometimes in half. The presented text discusses several such instances. The author concentrated predominantly on the functioning of the lethal frontier and the life of people residing on both its sides. He also described the history of Baarle–Hertog, a little– known fragment of free Belgium within Dutch Branat, and its role in obtaining information about the plans and activity of the German occupant.“
Keywords: Baarle-Hertog; Baarle-Nassau; Elektrozaun; Enklave; Erster Weltkrieg

Baarle in stukken. Fragmenten uit het verleden van Baarle, Castelre en Zondereigen - Jansen, Jos (Heemkundekring Amalia van Solms, Baarle-Hertog-Nassau, 1992)
Keywords: Baarle-Hertog; Baarle-Nassau; Enklave

De Belgische enclaves in Nederland. Bijdragen tot de rechtsgeschiedenis van Baarle-Hertog en Baarle-Nassau - Brekelmans, Franciscus Antonius (Bijdragen tot de geschiedenis van het zuiden van Nederland, 1965)
Keywords: Baarle-Hertog; Baarle-Nassau; Enklave; Hochschulschrift